The Comparative Study of Anti-inflammatory, Antioxidant and Antibacterial Effects with Regard to the Extraction Solvents of Cuscutae Semen - Hwang BoMin; Seo HyungSik (Korean Pharmacopuncture Institute, 2011)
Objective: This study was performed to compare anti-inflammation, anti-oxidation and anti-bacterial effects of Cuscutae Semen(CS) extracted with two kinds of solvents, ethanol and distilled water. Methods: Two kinds of CS extractions were prepared 20, 50, 100 ㎕/㎎. The cytotoxicity was measured by MTT assay in Raw 264.7 cell. The anti-inflammation effect was measured by inhibitory efficacy of NO Production in Raw 264.7 cell. The anti-oxidation effect was measured by DPPH Radical scavenging ability in HaCaT cell. The anti-bacterial effect was measured by inhibition zone diameter on Propionibacterium acnes. Results: 1. Two kinds(100 ㎍/㎖) of CS extraction groups had 50% cytotoxicity in Raw 264.7 cell. 2. All of CS extraction groups were not showed significantly inhibitory effect on NO production. 3. All of CS extracted with ethanol only showed dose-dependently significantly scavenging effect of DPPH radicals. 4. Two kinds of CS extractions did not have a inhibitory effect on Propionibactrium acnes. Conclusion: Two kinds(100 ㎍/㎖) of CS extraction groups have 50% cytotoxicity. Two kinds of CS extractions have not the inhibitory effect on NO production and Propionibactrium acnes. CS groups extracted with ethanol only have a significantly scavenging ability of DPPH radicals. This study suggests that CS extracted with ethanol was effective in anti-oxidation.